An epithelial biomarker signature for idiopathic pulmonary fibrosis: an analysis from the multicentre PROFILE cohort study - Maher, Toby M.; Oballa, Eunice; Simpson, Juliet K.; Porte, Joanne; Habgood, Anthony; Fahy, William A; Flynn, Aiden; Molyneux, Philip L.; Braybrooke, Rebecca; Divyateja, Hrushikesh; Parfrey, Helen; Rassl, Doris; et al. (Elsevier, 2017)
Background: Idiopathic Pulmonary Fibrosis (IPF) is a progressive, fatal condition with a variable disease trajectory. The aim of this study was to evaluate potential biomarkers that predict outcome for people with IPF. Method: The PROFILE study is a large prospective longitudinal cohort of treatment naïve IPF patients. We adopted a two-stage discovery and validation design using the PROFILE cohort. For the discovery analysis 106 individuals were examined alongside 50 age and gender matched healthy controls. We undertook an unbiased, multiplex evaluation of 123 biomarkers. Promising, novel, markers were further evaluated by immunohistochemical assessment of IPF lung tissue. The validation analysis examined samples from 206 IPF subjects, from the remaining 212 IPF patients recruited to PROFILE Central England, and were used for replication of the biomarkers identified from the discovery analysis using singleplex assays. This study addressed the predictive power of selected biomarkers to identify individuals with IPF at risk of: 1) progression and 2) death. The PROFILE studies are registered on clinicaltrials.gov (PROFILE Central England NCT01134822; PROFILE Royal Brompton Hospital NCT01110694). Findings: The discovery analysis identified four serum biomarkers (Surfactant Protein D, Matrix Metalloproteinase 7, CA19-9 and CA-125) suitable for replication. Histological assessment of CA19-9 and CA-125 established these proteins as markers of epithelial damage. Replication analysis confirmed that baseline values of SP-D (46.6ng/ml vs 34.6 ng/ml; p =0.002) and CA19-9 (53.7 U/ml vs 22.2 U/ml p<0.001) were significantly higher in patients with progressive disease, and rising levels of CA-125 over 3 months were associated with increased risk of mortality (HR 2.542 CI 1.493-4.328 p<0.001). Interpretation: We have identified serum proteins secreted from metaplastic epithelium that predict disease progression and death in IPF.